Surgeon’s preference of subcutaneous tissue resection: most important factor for short-term complications in subcutaneous implant placement after mastectomy : results of a cohort study - Pfob, André; Kölbel, Vivian; Schütz, Florian; Feißt, Manuel; Blumenstein, Maria; Hennigs, André; Golatta, Michael; Heil, Jörg (Archives of gynecology and obstetrics, 2020)
Little is known about the reason of high short-term complication rates after the subcutaneous placement of breast implants or expanders after mastectomy without biological matrices or synthetic meshes. This study aims to evaluate complications and their risk factors to develop guidelines for decreasing complication rates.